Cross-Madzhab Comparison of Fiqh as an Effort to Strengthen Religious Moderation in Islamic Religious Education - Shokhibul Mighfar (Aslim: Journal of Education and Islamic Studies, 2025)
Indonesian society is plural and requires a religious approach that is inclusive, tolerant, and balanced. Inter-sectarian comparison is considered important because it can demonstrate that the diversity of opinions in Islamic jurisprudence is an intellectual wealth of Islam that can promote moderation and prevent students from fanaticism. This study aims to analyze cross-sectarian comparative studies as an effort to strengthen religious moderation in Islamic Religious Education. This study uses a qualitative method with a Library Research approach. The results of the study show that religious moderation in Islam emphasizes the principles of tolerance, openness, and justice. In Islamic Religious Education, strengthening religious moderation can be done thru teacher example, implementation of a moderation-based curriculum, integration of moderate values into all materials, and dialogical and participatory teaching methods. Cross-madzhab comparative studies are relevant in shaping moderate attitudes because they provide a proportional understanding of the differences in scholars' opinions, thus fostering an inclusive perspective and preventing students from adopting fanaticism or claiming sole truth. Interfaith comparison should be positioned as a supporting means that enriches students' religious perspectives, not as an arena to emotionally sharpen sectarian differences. Thus, cross-madzhab comparative integration in Islamic Religious Education learning has the potential to strengthen students' characters to be more inclusive, tolerant, and capable of living harmoniously in a multicultural society.